The silent shield - Wheeler, Jeff, 1971- (Wheeler, Jeff, 1971- Kingfountain series., 2017)
Thrust into the heart of events threatening to rip her kingdom apart, young Trynne Kiskaddon will gain new powers and see old allies fall and new heroes rise as the battle for the kingdom and the lands beyond begins. Courtly intrigue and rumors of invasion plunge Kingfountain into turmoil as the search for Trynne's father begins in earnest. But Trynne's quest to learn the truth of Owen's sinister disappearance is sidetracked when tragedy strikes her family once again. Suddenly, the future of the kingdom rests in her hands as she struggles to learn--and control--the power that can keep the threatening Deep Fathoms at bay. When King Gahalatine unleashes his overwhelming forces against the realm, Trynne must draw on her political instincts, warrior training, and Fountain-blessed magic if she hopes to survive the chaos to come. But a final, epic confrontation will force Trynne into an unimaginable choice: save her kingdom and the lives of her people, or lose the one who means more to her than lfie itself.